The Influence of Risk, Location, and Relationship on Refusing an Event Invitation During the COVID-19 Pandemic - Bostwick, Eryn; Dunbar, Norah E.; Johnson, Amy Janan (Frontiers in Communication, 2022)
Viewed through the lens of the Revelation Risk Model (RRM), we examined whether the perceived riskiness of an activity, relationship type (family romantic, or friends), and location in the US (California, Oklahoma, or Ohio) influenced whether and how people communicated with close others when refusing an event invitation during the COVID-19 pandemic. Additionally, we examined how these factors affected their likelihood of attending an event, their likelihood of refusing an invitation, and their anticipation of the effect of the disclosure of their refusal on future interactions. States varied widely in their response to the pandemic and our results suggest this affected participants’ responses to the activity scenarios we presented. People from Ohio and California reported less likelihood of attending the event in the high-risk condition than people from Oklahoma. Participants were more likely to make up false excuses for low-risk events to avoid conflict. A three-way interaction between riskiness of the scenario, closeness of the relationship type, and location affected the effect on future interactions. Implications for the effects of refusals on relationships are discussed.